Attractiveness of host volatiles combined with background visual cues to the tea leafhopper, Empoasca vitis. Issue 3 (15th October 2015) - Cai, Xiao‐Ming; Xu, Xiu‐Xiu; Bian, Lei; Luo, Zong‐Xiu; Xin, Zhao‐Jun; Chen, Zong‐Mao
Abstract: The tea green leafhopper, Empoasca vitis (Göthe) (Hemiptera: Cicadellidae), is a serious pest of tea plants. We examined the behavioral responses of E. vitis adults to odors from the shoots of three host plants in a Y‐tube olfactometer with background visual cues. The host plants were tea [ Camellia sinensis (L.) Kuntze (Theaceae)], peach [ Prunus persica (L.) Siebold & Zucc. (Rosaceae)], and grapevine [ Vitis vinifera L. (Vitaceae)]. Volatiles from the shoots were analyzed. Both yellow‐green and gold backgrounds enhanced the olfactory responses of E. vitis adults to tea plant odors, and this enhancement was stronger under a high light intensity. On the yellow‐green background, E. vitis adults significantly preferred the odors from shoots of the three host plants compared with clean air. Moreover, E. vitis adults preferred grapevine odor over the tea plant odor. The volatile blends of the three plant species were distinctly different. Peach plant shoots emitted the greatest amount of volatiles, whereas grapevine shoots released the greatest diversity of compounds. These results provide evidence that background visual cues could enhance the response of E. vitis adults to host‐plant volatiles. The leafhoppers can discern different host odors, suggesting the possibility of using peach plant and grapevine odors to monitor and manage this pest in tea plantations.